After the JD, Wave 3: A Longitudinal Study of Careers in Transition, 2012-2013, United States - Nelson, Robert ([Verlag nicht ermittelbar], 2014)
The After the JD (AJD) project is a longitudinal study that was designed to track the careers of a nationally representative cohort of lawyers admitted to the bar in the year 2000. This collection is the third wave of the After the JD Project. The first wave of the After the JD project (AJD1) [ICPSR 26302] provided a snapshot of the personal lives and careers of this cohort about three years after they began practicing law. The second wave of the After the JD project (AJD2) [ICPSR 33584] sought to illuminate the progression of lawyers' careers through roughly seven years in practice. The third wave (AJD3) continued to shed light on lawyers' 12-year professional and personal pathways. After 12 years, the AJD lawyers had a decade of work experience behind them, and the contours of their careers were more clearly shaped. Throughout their professional careers, these lawyers had experienced important transitions (such as promotion to partnership, marriage, and job changes), which were only in process by Wave 2. AJD3 marked a significant milestone, essential to assess the personal and career trajectories of this cohort of lawyers. AJD3 sought to locate and survey only individuals who had previously responded to either AJD1 or AJD2. Sample members who never responded to any survey wave were not located in AJD3. The AJD3 data collection started in May 2012 and was completed in early 2013. The dataset allowed for the analysis of a broad range of questions about the careers of lawyers and the social organization of the American legal profession. Topics covered include current professional employment, impact of economic downturn, type of work, clients, mentors, employment history, social, political, and community participation, and background and family information. Demographics include ethnicity, employment status, sexuality, marital status, age, and gender.